Internet design in a modern educational environment - Alieva, Zainab K.; Vaganova, Olga I.; Kirillova, Inna K.; Tsarapkina, Julia M.; Sesorova, Olga V. (Journal of the University of Zulia, 2021)
Purpose of the article: analysis of the process of Internet design in the modern educational environment. Methodology: The article presents the results of a survey of students of higher educational institutions “Assessment of the impact of Internet projects on professional self-development", about the dynamics of the participation of students from professional educational institutions in the design of the Internet for three years. Conclusions. According to the research, the number of participants in Internet projects is growing, and the popularity of such contests is increasing. Participation in the Internet project provides the student an opportunity for promising employments.